Manajemen Usaha Dan Produksi Pada Usaha Mikro, Kecil Dan Menengah (UMKM) Di Desa Carang Wulung Wonosalam - Abdul Rohim; Indara Kurniawan (STIE PGRI Dewantara Jombang, 2017)
AbstractThe mentoring activity conducted in January - March 2017 in Carang Wulung village, Wonosalam Jombang, is aimed to help the economic empowerment of the community, especially processed chips with basic ingredients of banana and taro. This activity involves 2 (two) partners who have the will and are willing to become partners. Types of mentoring include coaching in the areas of: a) Training & Assistance of Business Management, b) Training & Assistance of Packaging, Branding, & Labeling, c) Training & Facilitation of Banking Capital Access, d) Training & Mentoring. At the end of the activity, the two partners have been able to absorb and practice what has been delivered by the counterpart team so that the efforts of both partners to be better.Keywords: Assistance, processed foods, banana chips, taro.